Investigating on the Impact of Software Clones on Technical Debt - Lerina, Aversano; Nardi, Laura (2019 IEEE/ACM International Conference on Technical Debt (TechDebt), 2019)
Code reuse by copying a code fragment with or without modification generates duplicate copies of exact or similar code fragments in a software system, known as code clones. The debate about the harmfulness of clone in ongoing in the literature, nevertheless, it is widely recognized that clones needs special considerations during software evolution. In this paper, it is proposed a quantitative analysis of technical debt values to understand if it is higher with cloned code than those without cloned code. Moreover, changes performed on these files have been analyzed by analyzing commit logs. According to our inspection on four subject systems, the technical debt of files with cloned code is significantly higher than those without cloned code. Moreover, as expected, files with cloned code are more impacted by changes.